Battra: The Traditional Knowledge Holder on Medicinal Plant among People of East Lampung, Indonesia: Battras: Holders of Traditional Medicinal Plant Knowledge - Yudiyanto, Yudiyanto; Wakhidah, Anisatu Z.; Abdullah, Irwan; Indiyanto, Agus (Journal of Tropical Life Science, 2024)
Local knowledge continues to experience two fundamental problems that cause its existence to be marginalized and cannot be widely passed on. Externally, local knowledge has always been questioned for its relevance to the times. Internally, it has become elitist, making it difficult for other groups to access it. Gradually, local knowledge is alienated in people's lives. To date, ethnobotany studies have focused on identifying plants and their properties for policy and business purposes. This study was carried out in four old villages near the Way Kambas National Park, East Lampung, which were selected using the purposive sampling method. The key respondents were selected using the snowball sampling method, while data were collected from respondents through semi-structured interviews. Selected medicinal plants were observed, and the data were analyzed qualitatively and descriptively. Interviews with parties interested in medicinal plant knowledge show the monopolistic mastery of knowledge by all parties and their interests. The study shows a great need for synergy between parties for the preservation of medicinal plant knowledge, starting with the opening of access to knowledge for all. The openness of the battras  (traditional healers) to share sources of knowledge, the dedication of researchers/scientists in transforming knowledge into the public domain, the willingness of the private sector to share the value of medicinal plants benefits, and a pro-people policy framework will be key to the sustainability of medicinal plant knowledge for the development of fair and dignified public health.